Pelatihan Pembuatan Eco-enzyme sebagai Handsanitizer di RT.001/008 Kelurahan Bulakrejo Kecamatan Sukoharjo Kabupaten Sukoharjo dalam Upaya Mewujudkan Desa Mandiri Tangguh Covid-19 - Tri Wiharti; Nur Rokhimah Hanik; Ratna Dewi Eskundari (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
The Covid-19 pandemic which has lasted for about 2 years has had a negative impact in almost all parts of the world, including in this partner communities. This community service activity aims to provide training to partner communities regarding the manufacture of one of the ecoenzyme diversification products in the form of an eco-handsanitizer. This activity has a sequence of situation analysis of partner communities, counseling and training on making eco-handsanitizer, and evaluation. The evaluation results showed that the community partners can make eco-handsanitizers after this outreach.